Pengaruh Terpaan Pemberitaan Unilever Terhadap Minat Beli Produk Unilever Pasca-Boikot (Studi pada Warga RT 007/RW 001 Palmerah, Jakarta Barat) - Malik, Muhammad; Yulistiani, Indriati; Naning, Salman (Indonesian Journal Publisher, 2026)
This study aims to analyze the effect of exposure to Unilever boycott news on consumer purchasing interest among residents of RT 007/RW 001 Palmerah, West Jakarta. The study used an explanatory quantitative approach with a purposive sampling technique. A total of 86 respondents were selected from a population of 109 heads of families based on the Slovin formula. Data were collected through questionnaires and analyzed using simple linear regression with the help of SPSS 25. The results showed that exposure to news had a negative and significant effect on purchasing interest (t = –6.197) (p < 0.001). The coefficient of determination (R²) value of 0.339 indicates that 33.9% of the variation in purchasing interest is explained by exposure to news, while 66.1% is influenced by other factors. A regression coefficient of –0.576 indicates that the higher the exposure to boycott news, the lower consumer purchasing interest. Thus, exposure to boycott news has been shown to significantly reduce purchasing interest, confirming that media messages can influence consumer attitudes and behavioral tendencies. These findings indicate that the quality and relevance of news content play an important role in shaping consumer behavior, so that the stronger and more meaningful the message received, the greater the potential for increased purchasing interest.